Perovskite solar cell with sandwich structure metal electrode
By adopting metal electrodes with sandwich structure in perovskite solar cells, the problem of poor stability of perovskite solar cells is solved, higher stability and service life are achieved, and production costs are reduced.
Patent Information
- Application Number
- CN202421232390.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Utility models(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2034-05-31
AI Technical Summary
Perovskite solar cells have poor stability and low weather resistance, and are susceptible to temperature, water and oxygen, resulting in material cracking and degradation of battery performance.
Metal electrodes with sandwich structure, including electrode protective film layer, alloy electrode and buffer coating layer, are made by vacuum magnetron sputtering coating technology to enhance the stability of the electrode and prevent water vapor from entering.
It improves the stability and service life of perovskite solar cells, extends the reliability of the battery, and reduces production costs.
Smart Images

Figure CN222827616U_ABST
Abstract
Description
Technical Field
[0001] The utility model relates to the field of solar cells, in particular to a perovskite solar cell with a sandwich structure metal electrode. Background Art
[0002] Solar energy is a renewable, clean energy source that is of great significance to the sustainable development of mankind. Solar cells convert solar energy into electrical energy. The conversion efficiency, materials and manufacturing costs of solar cells are key factors in determining their industrial application, grid parity and the ultimate goal of energy substitution. At present, silicon-based solar cells occupy more than 95% of the market, but it is becoming increasingly difficult to continuously improve their conversion efficiency. Perovskite solar cells are the fastest-growing solar cell technology in recent years, with their efficiency increasing from the initial 3.8% to the current 26.15%. Perovskites also have the characteristics of adjustable bandgap width, simple preparation process and low cost.
[0003] Perovskite materials are a class of materials with the same crystal structure as calcium titanate (CaTiO3). They were discovered by Gustav Rose in 1839 and later named by Russian mineralogist LA Perovski. The structural formula of perovskite materials is generally ABX3, where A and B are two cations and X is an anion. This unique crystal structure gives it many unique physical and chemical properties, such as absorption, rotation, optical activity, electrocatalysis, etc., and has many applications in the fields of chemistry and physics. A is an organic cation, usually an aliphatic or aromatic ammonium, B is a divalent metal cation, such as Ge2+, Sn2+, Pb2+, etc., and X is a halogen anion (Cl-, Br-, I-) [5]. In 2009, Tsutomu Miyasaka first selected organic-inorganic hybrid perovskite materials CH3NH3PbI3 and CH3NH3PbBr3 to replace the dyes in traditional DSSCs as new photosensitizers to prepare the first true perovskite solar cell. After nearly ten years of development, the conversion efficiency of this solar cell has been able to reach more than 25% in the laboratory, and its low cost is its advantage.
[0004] Perovskite solar cells are solar cells that use perovskite-type organic metal halide semiconductors as light-absorbing materials and belong to the third generation of solar cells. Perovskite technology has attracted much attention due to its advantages such as low cost, low energy consumption, light weight and flexible manufacturing. It is also called "new concept solar cells" and has become the "top stream" in the current photovoltaic field. Although the efficiency of perovskite cells has increased rapidly in recent years, they still have the disadvantages of poor stability and low weather resistance. The main reason is that perovskite materials are easily affected by temperature, moisture and oxygen. How to improve the stability of the battery is the current focus of research and development. Utility Model Content
[0005] The utility model aims to provide a perovskite solar cell with a sandwich structure metal electrode, which has high stability, can block water vapor from entering the interior, delay the decomposition of the perovskite material, and help to increase the service life of the battery.
[0006] The above-mentioned optimized structure of the utility model is realized by the following technical scheme: a perovskite solar cell with a sandwich structure metal electrode, comprising an electrode protective film layer, an alloy electrode, a buffer coating layer, an electron transport layer II, an electron transport layer I, a perovskite absorption layer, a hole transport layer II, a hole transport layer I, and a transparent conductive coated glass;
[0007] The electrode protection film layer, the alloy electrode, the buffer coating layer, the electron transport layer II, the electron transport layer I, the perovskite absorption layer, the hole transport layer II, the hole transport layer I, and the transparent conductive coated glass are connected in sequence from top to bottom.
[0008] In some embodiments, the electrode protection film layer is vacuum sputtered copper-nickel alloy, nickel-chromium alloy or titanium alloy, with a thickness of 10-100 nm and a resistivity of <7×10-6Ωcm.
[0009] In some embodiments, the alloy electrode is vacuum sputtered copper-nickel alloy, copper-zirconium or copper-zirconium alloy; its thickness is 30-200 nm and its resistivity is <6×10-6Ωcm.
[0010] In some embodiments, the buffer coating layer is vacuum sputtered copper-nickel alloy, nickel-chromium alloy, titanium alloy, pure chromium, indium tin oxide material, indium zinc oxide material and zinc aluminum oxide; its thickness is 10-50nm, and its resistivity is less than 7×10-6Ωcm.
[0011] In some embodiments, the electron transport layer II is formed by sputtering zinc magnesium oxide, zinc tin oxide, titanium oxide, aluminum oxide or tin oxide using linear gas flow plasma, and has a thickness of 5-50 nm.
[0012] In some embodiments, the electron transport layer I is a C60 film layer or a LiF film layer manufactured by linear thermal evaporation, and has a thickness of 5-30 nm.
[0013] In some embodiments, the perovskite absorption layer is a perovskite absorption layer made by linear thermal evaporation; a Cs, FA, MA mixed cation perovskite material is used, the band gap range is 1.65~1.70eV, and the thickness is 100-1000nm.
[0014] In some embodiments, the hole transport layer II is a thin film layer formed by vacuum magnetron sputtering of copper aluminum oxide, copper chromium oxide, strontium copper oxide, copper gallium oxide, or copper indium oxide, and has a thickness of 5-50 nm.
[0015] In some embodiments, the hole transport layer I is a thin film layer formed by vacuum magnetron sputtering of nickel oxide, nickel magnesium oxide, nickel copper oxide, nickel lithium oxide, copper oxide or cuprous oxide, and has a thickness of 5-50 nm.
[0016] In some embodiments, the transparent conductive coated glass is made of indium tin oxide, zinc aluminum oxide, zinc aluminum gallium oxide, indium hafnium oxide, indium zirconium oxide, indium zinc oxide, indium tin zinc oxide, indium tungsten oxide, tin oxyfluoride or indium titanium oxide on photovoltaic glass using vacuum sputtering physical deposition, with a thickness of 50-200nm and a resistivity of less than 5×10-4Ωcm.
[0017] In summary, the utility model has the following beneficial effects:
[0018] The electrode protection film layer, alloy electrode and buffer coating layer in the perovskite solar cell with sandwich structure metal electrode are all made by vacuum magnetron sputtering coating. The buffer coating layer can increase the adhesion between the electron transport layer and block the diffusion of copper atoms into the internal film layer, thereby improving the stability of the film layer. The alloy electrode made of copper alloy can reduce the thermal expansion and contraction characteristics of pure copper, improve the oxidation resistance, and maintain long-term stability. The electrode protection film layer is made of copper-nickel alloy, which can block the entry of water vapor and prevent the oxidation and degradation of the alloy electrode. The better conductivity also reduces the impedance of the interface.
[0019] The utility model adopts an electrode protection film layer, an alloy electrode and a buffer coating to form a metal electrode with a sandwich structure, which has high stability, can block water vapor from entering the interior, delay the cracking of the perovskite material, and help to increase the service life of the battery; the sandwich metal electrode is mainly made of copper and nickel metal materials, which are much cheaper than precious metals such as gold and silver, and adopts traditional vacuum magnetron sputtering, which can maintain uniformity over a large area, and the equipment investment cost is also low. The metal electrode with a sandwich structure has a high reflectivity and can improve the conversion efficiency of the battery, thereby reducing the overall production cost. Due to the improvement in reliability, the service life is extended, which is conducive to market promotion and product popularization. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a structural schematic diagram of the utility model.
[0021] In the figure: 1. Electrode protection film layer; 2. Alloy electrode; 3. Buffer coating layer; 4. Electron transport layer II; 5. Electron transport layer I; 6. Perovskite absorption layer; 7. Hole transport layer II; 8. Hole transport layer; 9. Transparent conductive coated glass. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the utility model to clearly and completely describe the technical solutions in the embodiments of the utility model. Obviously, the described embodiments are only part of the embodiments of the utility model, not all of them. Based on the embodiments of the utility model, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.
[0023] refer to Figure 1 A perovskite solar cell with a sandwich structure metal electrode includes an electrode protection film layer 1, an alloy electrode 2, a buffer coating layer 3, an electron transport layer II4, an electron transport layer I5, a perovskite absorption layer 6, a hole transport layer II7, a hole transport layer I8, and a transparent conductive coated glass 9 connected in sequence from top to bottom. The electrode protection film layer 1, the alloy electrode 2, and the buffer coating layer 3 form a sandwich structure motor, which has high stability, can block water vapor from entering the interior, delay the decomposition of the perovskite material, and help to increase the service life of the battery.
[0024] The electrode protection film layer 1 is vacuum sputtered copper-nickel alloy, nickel-chromium alloy or titanium alloy, with a thickness of 10-100 nm and a resistivity of less than 7×10-6Ωcm.
[0025] The alloy electrode 2 is made of vacuum sputtered copper-nickel alloy, copper-chromium alloy or copper-zirconium alloy; its thickness is 30-200nm and its resistivity is less than 6×10-6Ωcm.
[0026] The buffer coating layer 3 is made of vacuum sputtered copper-nickel alloy, nickel-chromium alloy, titanium alloy, pure chromium, indium tin oxide (ITO), indium zinc oxide (IZO) and aluminum zinc oxide (AZO); its thickness is 10-50nm and its resistivity is less than 7×10-6Ωcm.
[0027] The electron transport layer II4 is a thin film layer formed by linear gas flow plasma sputtering of materials such as zinc magnesium oxide (ZnMgO), zinc tin oxide (ZTO), titanium oxide (TiO2), aluminum oxide (Al2O3) or tin oxide (SnO2), and its thickness is 5-50nm.
[0028] The electron transport layer I5 is made of a C60 film or a LiF film by linear thermal evaporation, and its thickness is 5-30nm.
[0029] The perovskite light absorbing layer 6 may be a perovskite light absorbing layer made by linear thermal evaporation; a Cs, FA, MA mixed cation perovskite material may be used, with a band gap range of 1.65-1.70 eV and a thickness of 100-1000 nm.
[0030] The hole transport layer II7 can be a thin film layer formed by vacuum magnetron sputtering of materials such as copper aluminum oxide (CuAlO2), copper chromium oxide (CuCrO2), strontium copper oxide (SrCuO2), copper gallium oxide (CuGaO2), or copper indium oxide (CuInO2), and its thickness is 5-50nm.
[0031] The hole transport layer I8 may be a thin film layer formed by vacuum magnetron sputtering of nickel oxide (NiO), nickel magnesium oxide (NiMgO), nickel copper oxide (NiCuO), nickel lithium oxide (NiLiO), copper oxide (CuO) or cuprous oxide (Cu2O) and the like, and its thickness is 5-50 nm.
[0032] The transparent conductive coated glass 9 can be made of indium tin oxide (ITO), aluminum zinc oxide (AZO), aluminum zinc oxide (GAZO), hafnium indium oxide (IHO), zirconium indium oxide (IZrO), indium zinc oxide (IZO), indium tin zinc oxide (IZTO), indium tungsten oxide (IWO), tin fluoride oxide (FTO) or indium titanium oxide (ITiO) on photovoltaic glass by vacuum sputtering physical deposition, with a thickness of 50-200nm and a resistivity of less than 5×10-4Ωcm.
[0033] The specific production process is as follows:
[0034] For the production of transparent conductive coated glass 9, after the background pressure of the vacuum magnetron sputtering chamber is pumped down to 0.7×10-5~0.9×10-5torr by a vacuum pumping system, a target material such as indium tin oxide (ITO), aluminum zinc oxide (AZO), aluminum zinc gallium oxide (GAZO), indium hafnium oxide (IHO), indium zirconium oxide (IZrO), indium zinc oxide (IZO), indium tin zinc oxide (IZTO), indium tungsten oxide (IWO), tin fluoride oxide (FTO) or indium titanium oxide (ITiO) is used to sputter a film on the photovoltaic glass, and the film thickness is 50-200nm and the resistivity is less than 5×10-4Ωcm
[0035] For the production of the hole transport layer I8, after the background pressure of the vacuum magnetron sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum pumping system, nickel oxide (NiO), nickel magnesium oxide (NiMgO), nickel copper oxide (NiCuO), nickel lithium oxide (NiLiO), copper oxide (CuO) or cuprous oxide (Cu2O) and other material thin film layers are sputtered and deposited on the transparent conductive glass 9. The thickness of the thin film layer is 5-50nm, thereby completing the production of the hole transport layer I8.
[0036] For the preparation of the hole transport layer II7, after the background pressure of the vacuum magnetron sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum pumping system, copper aluminum oxide (CuAlO2), copper chromium oxide (CuCrO2), strontium copper oxide (SrCuO2), copper gallium oxide (CuGaO2), or copper indium oxide (CuInO2) thin film layers with a thickness of 5-50nm are sputtered and deposited on the hole transport layer I8 using targets such as copper aluminum oxide (CuAlO2), copper chromium oxide (CuCrO2), strontium copper oxide (SrCuO2), copper gallium oxide (CuGaO2), or copper indium oxide (CuInO2). The thickness of the thin film layers is 5-50nm, thereby completing the preparation of the hole transport layer II7.
[0037] For the preparation of the perovskite light-absorbing layer 6, the Cs, FA, and MA mixed cation perovskite material is placed in a metal crucible of a linear thermal evaporation device. After the background pressure of the sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum exhaust system, the linear metal crucible is heated to about 250°C to allow the material to be thermally evaporated and attached to the hole transport layer II8, thereby completing the preparation of the perovskite light-absorbing layer 6, which has a thickness of 100-1000nm.
[0038] For the preparation of the electron transport layer I5, C60 or LiF material is placed in a metal crucible of a linear thermal evaporation device. After the background pressure of the sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum exhaust system, the linear metal crucible is heated to about 300-500°C to allow the material to be thermally evaporated and attached to the perovskite light absorption layer 6, thereby completing the preparation of the electron transport layer I5, which has a thickness of 5-30nm.
[0039] For the production of electron transport layer II4, linear gas flow plasma sputtering is used. After the vacuum exhaust system evacuates the background pressure of the sputtering chamber to 0.7×10-5-0.9×10-5torr, argon is used as the working gas. The argon is introduced through a throttle valve to control the working pressure of the sputtering chamber to 3×10-3torr. Zinc magnesium oxide (ZnMgO), zinc tin oxide (ZTO), titanium oxide (TiO2), aluminum oxide (Al2O3) or tin oxide (SnO2) and other materials are used. On the electron transport layer I5, thin films such as zinc magnesium oxide (ZnMgO), zinc tin oxide (ZTO), titanium oxide (TiO2), aluminum oxide (Al2O3) or tin oxide (SnO2) are sputtered with a thickness of 5-50nm, thereby completing the production of electron transport layer II4.
[0040] For the production of buffer coating layer 3, after the background pressure of the vacuum magnetron sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum pumping system, copper-nickel alloy, nickel-chromium alloy, titanium alloy, pure chromium, indium tin oxide material (ITO), indium zinc oxide material (IZO) and zinc aluminum oxide (AZO) and other target materials are used; a film is sputtered on the electron transport layer II4, and the film thickness is 10-50nm and the resistivity is less than 7×10-6Ωcm.
[0041] For the production of the alloy electrode 2, the background pressure of the vacuum magnetron sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum pumping system, and then a target material such as copper-nickel alloy, copper-chromium alloy or copper-zirconium alloy is used; a film is sputtered on the buffer coating 3, and the film thickness is 50-200nm and the resistivity is less than 6×10-6Ωcm.
[0042] For the production of the metal protective layer 1, the background pressure of the vacuum magnetron sputtering chamber is evacuated to 0.7×10-5~0.9×10-5torr by a vacuum pumping system, and then a target material such as copper-nickel alloy, nickel-chromium alloy or titanium alloy is used; a film is sputtered on the electron transport layer II4, and the film thickness is 10-100nm and the resistivity is less than 7×10-6Ωcm.
[0043] Completing the above process means completing the production of a new type of perovskite solar cell with a sandwich structure metal electrode.
[0044] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A perovskite solar cell with a sandwich structure metal electrode, characterized in that: It comprises an electrode protection film layer (1), an alloy electrode (2), a buffer coating layer (3), an electron transport layer II (4), an electron transport layer I (5), a perovskite absorption layer (6), a hole transport layer II (7), a hole transport layer I (8), and a transparent conductive coated glass (9); The electrode protection film layer (1), the alloy electrode (2), the buffer coating layer (3), the electron transport layer II (4), the electron transport layer I (5), the perovskite absorption layer (6), the hole transport layer II (7), the hole transport layer I (8), and the transparent conductive coated glass (9) are connected in sequence from top to bottom.
2. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The electrode protection film layer (1) is vacuum sputtered copper-nickel alloy, nickel-chromium alloy or titanium alloy, with a thickness of 10-100 nm and a resistivity of <7×10-6Ωcm.
3. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The alloy electrode (2) is a vacuum sputtered copper-nickel alloy, copper-zirconium or copper-zirconium alloy; its thickness is 30-200 nm and its resistivity is less than 6×10-6 Ωcm.
4. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The buffer coating layer (3) is vacuum sputtered copper-nickel alloy, nickel-chromium alloy, titanium alloy, pure chromium, indium tin oxide material, indium zinc oxide material and zinc aluminum oxide; its thickness is 10-50nm, and its resistivity is less than 7×10-6Ωcm.
5. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The electron transport layer II (4) is made of zinc magnesium oxide, zinc tin oxide, titanium oxide, aluminum oxide or tin oxide by linear gas flow plasma sputtering, and has a thickness of 5-50 nm.
6. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The electron transport layer I (5) is a C60 film layer or a LiF film layer made by linear thermal evaporation, and has a thickness of 5-30 nm.
7. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The hole transport layer II (7) is a thin film layer formed by vacuum magnetron sputtering of copper aluminum oxide, copper chromium oxide, strontium copper oxide, copper gallium oxide, or copper indium oxide, and has a thickness of 5-50 nm.
8. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The hole transport layer I (8) is a thin film layer formed by vacuum magnetron sputtering of nickel oxide, nickel magnesium oxide, nickel copper oxide, nickel lithium oxide, copper oxide or cuprous oxide, and has a thickness of 5-50 nm.
9. The perovskite solar cell with a sandwich structure metal electrode according to claim 1, characterized in that: The transparent conductive coated glass (9) is made of indium tin oxide, zinc aluminum oxide, zinc aluminum gallium oxide, indium hafnium oxide, indium zirconium oxide, indium zinc oxide, indium tin zinc oxide, indium tungsten oxide, tin fluoride oxide or indium titanium oxide on photovoltaic glass by vacuum sputtering physical deposition, and has a thickness of 50-200 nm and a resistivity of less than 5×10-4 Ωcm.